Compassion, pride, and social intuations of self-other similarity.[article]. - Oveis, Christopher
Compassion and pride serve contrasting social functions : Compassion motives care-taking behavior, whereas pride enables the signaling and negotiation of rank within social hierarchies. Across studies, compassion was associated with increase perceived self-other similarity, particularly to weak or vulnerable others. In contrast, pride was associated with an enhanced sense of similarity to strong others, and a sense of similarity to weak others. These findings were obtained using trait measures (Study 1) and experimental inductions (Study 2 and 30 of compassion and pride, examining the sense of similarity to strong or weak groups (Studies 1 and 2) and unfamiliar individuals (Study 3). The positive mood, nor was this effect constrained by the ingroup status of the target group or individual. Discussion focuses on the contributions these findings make to an understanding of compassion and pride.